Anesthetic Considerations for Electrophysiologic Studies and Catheter Ablations - Mary Arthur; Nadine Odo; Adam Berman (MedEdPORTAL, 2010)
Abstract With increasingly complex electrophysiologic procedures, particularly in patients with complex cardiovascular disease, the presence of an anesthesiologist in the electrophysiology lab has become more important. Anesthesiologists currently in training are likely to be involved in such procedures. This resource is intended to give anesthesia providers, including residents, medical students, and faculty, a better understanding of the basics of electrophysiologic procedures, the varied responses of both normal and abnormal myocardial tissue to volatile and intravenous anesthetic agents, and the anesthetic equipment required for the electrophysiology lab. This resource can be presented in 20 to 45 minutes, depending on the experience of the students. We have been able to successfully implement this program by using it as a training resource for faculty, residents, and medical students. For residents, training shortly before their scheduled time in the electrophysiologic lab will help to ensure retention of the information learned.